Astrocytes and diffusive spread of substances in brain extracellular space - Sherpa, Ang D.; Hrabetova, Sabina (Diffusion Fundamentals, 2016)
Brain function is based on communication between individual cells, neurons and glia. From a traditional point of view, neurons play a central role in the fast transfer of information in the central nervous system while astrocytes, major type of glia, serve as housekeeping elements maintaining homeostasis of the extracellular microenvironment. This view has dramatically changed in recent years as many findings ascribe new roles to astrocytes. It is becoming evident that astrocytes communicate with neurons via chemical signals released to the extracellular space (ECS). Astrocytes also have communication systems of their own, such as calcium waves that use gap junctions in combination with purinergic signaling through the ECS. Here we discuss yet another important role for astrocytes: that they regulate diffusion of signaling molecules and therapeutic agents in the extracellular microenvironment by contributing to the structural properties of ECS. There is a wealth of morphological data showing that each astrocyte is an exclusive occupant of a small volume of brain tissue, and that many fine astrocytic processes ensheathe neuronal processes and bodies. The functional significance of these unique morphological features is largely unknown with the exception of astrocytic coverage of synaptic formations. At the synapses, astrocytic processes play an active role by restricting neurotransmitter diffusion to the synaptic cleft and its immediate vicinity. Recent work suggests that astrocytic processes work in a similar fashion throughout the ECS and thus control the diffusive spread of substances over both short and long distances.